Fighting Coronavirus One Personality at a Time: Need for Structure, Trait Victimhood, and Adherence to COVID-19 Health Guidelines - Maaravi, Yossi; Hameiri, Boaz; Gur, Tamar (Frontiers in Psychology, 2020)
Following the outbreak of the COVID-19 pandemic, authorities have issued several guidelines to curb the pandemic’s disastrous effects. However, measures’ effectiveness is dependent upon people’s adherence to them. Therefore, it is crucial to understand the potential factors that explain guideline adherence. In the present brief research report, we investigated need for closure and trait victimhood - i.e., the tendency to feel like a victim – and their effect on fear of the pandemic, which in turn, predicted guideline adherence. Furthermore, the association between fear and guideline adherence was shaped by participants’ global self-efficacy: higher levels of self-efficacy predicted more guideline adherence regardless of fear levels. The present findings may be relevant to health messaging endeavors aiming to improve compliance with guidelines.